Personalidade autoritária, educação e democracia em Adorno - Ramos, Tadeu Alan (2020)
The goal of this dissertation is to show that the writings about education in the late thought of Adorno retake fundamental aspects developed on studies about the authoritarian personality in the beginning of the 1950’s aiming to highlight the centrality of childhood care for education and for democracy. The research problem is centered around the following question: what is the importance of understanding the concept of authoritarian personality for fulfilling the requirement that Auschwitz is not repeated, having as reference the childhood care aiming to an educational perspective aimed to the democratic experience in the current educational setting? The study was made from a bibliographic research, of hermeneutic character, comparing texts of Adorno in two different periods, specifically the Study texts about authoritarian personality and Essays about social psychology and psychoanalysis with the texts collected in the collection of Education and Emancipation. From the studies about authoritarian personality, aspects of those studies important for understanding their late writings about Education were sought. In the first chapter, I make introductory considerations regarding studies about the authoritarian personality in Adorno. In the second one, I rebuild the central theses about the theme of authoritarian personality, the fascist propaganda and the indications in those studies in education for emancipation. In the third one, I present the trajectory of the F scale, the theme of authoritarianism in the late Adorno thought and the education of the childhood for democracy. Finally, it is concluded that the aspects of the authoritarian personality, identified by means of the F scale in studies made by the group of Berkeley, are important for us to understand the repercussion about how a formation with failures in childhood, such as the difficulty in elaborating internal moral agencies in the conscience may result in problems for the future social life of individuals, complicating the creation of conditions for a democratic life. According to this educational perspective in Adorno, someone who learns, early, to give less highlight to the uncritical obedience, than to have a greater acceptance of different manifestations and expressions, formed based on affectionate and tolerant relationships, tends to choose a more democratic way of life in adulthood, able to resist to dominant heteronymous structures of the social sphere and not to blindly adhere to the collectives.